Pola Pemberian Makan Berhubungan dengan Kejadian Stunting Balita 12-59 Bulan di Wilayah Puskesmas Tamalanrea Makassar - Ira Wirya Wirawanti; Nadimin Nadimin; Sirajuddin Sirajuddin; Thresia Dewi; St. Marwati (Direktorat Politeknik Kesehatan Makassar, 2024)
The prevalence of stunting in the City of Makassar increased from 2022 to 2023. This is in contrast to the government's target to reduce stunting. Parenting patterns are parenting practices that influence a child's growth. One form of them is the feeding practices for toddlers. This research aimed to analyze the relationship between feeding practices and the incidence of stunting in 12-59 months toddlers at Tamalanrea Community Health Center Area. Research used quantitative methods with a cross sectional design on 53 samples of toddlers aged 12-59 months with respondents being mothers of toddlers. Samples were taken using a purposive sampling technique according to the inclusion criteria, toddlers who live in the Tamalanrea Health Center work area; aged 12-59 months; and cared for by mothers as primary caregivers. The exclusion criteria included toddlers with chronic diseases such as congenital heart disease, genetic disorders, allergies, and other chronic diseases that can affect linear growth; toddlers with autism or mental retardation; and mothers who refused to participate in the study. Data on the nutritional status of toddlers was collected by measuring body length using an infantometer or height using a stadiometer and data on feeding practices by mothers were collected using FPSQ. The results showed that the percentage of respondents with low feeding practices was 33%, 20% in mothers with stunted toddlers and 13% in mothers with normal toddlers. There was a significant relationship between feeding practices and stunting in toddlers (p = 0.001) with an inverse relationship and moderate level (r=-0.446). The conclusion was the better feeding practices given the lower incidence of stunting in toddlers. This implied the importance of education on feeding practices for mothers of toddlers so that mothers can apply good feeding practices to toddlers in everyday life, in the Tamalanrea Makassar Health Center area, to prevent stunting. Keywords : Feeding practices; Mothers of toddlers; Stunting; Toddlers